2003
DOI: 10.1063/1.1573363
|View full text |Cite
|
Sign up to set email alerts
|

Ion acceleration with ultrafast lasers

Abstract: Hot-electron confinement can build up fields capable of accelerating ions up to MeV energies when an ultrashort 35-fs laser pulse at ∼2×1018 W/cm2 interacts with a small spherical target. Singly charged ions with different masses have similar energies. A simple phenomenological model describes how ultrashort and less-energy-consumptive pulses drive ions to MeV energies. The energetic and spatial-emission characteristics of protons, deuterons and oxygen ions released from water and heavy-water droplets of ∼15 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Spectral dips [91,92] or even quasi-monoenergetic features [15,16] were seen in the measurements. This behavior is fluctuating from shot to shot since it highly depends on laser parameters [16].…”
Section: Quasi-monoenergetic Deuteron Burstsmentioning
confidence: 82%
See 3 more Smart Citations
“…Spectral dips [91,92] or even quasi-monoenergetic features [15,16] were seen in the measurements. This behavior is fluctuating from shot to shot since it highly depends on laser parameters [16].…”
Section: Quasi-monoenergetic Deuteron Burstsmentioning
confidence: 82%
“…Since the droplet is not grounded directly the sheath spreads around the droplet while decreasing. Due to the spherical symmetry protons are accelerated over the full solid angle while modifications of isotropic emission have been observed [91,101,121]. Furthermore, electrons produced at the front side can reach the rear side by passing around the droplets which may lead to an additional enhancement of the electrostatic field on the rear side [15].…”
Section: Proton Images Of Irradiated Water Dropletsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several experiments [4][5][6][7][8][9] and particle-in-cell (PIC) simulations [10][11][12][13][14][15] it has been shown that ions with MeV energies can be obtained from the interaction of femtosecond laser pulses with solid targets [16][17][18][19][20], gas jets [21,22] and clusters [23]. The ions are accelerated by either a Coulomb field via charge separation, a shock wave, or an electrostatic field at the rear side of the target.…”
Section: Introductionmentioning
confidence: 99%